2014
DOI: 10.3402/meo.v19.24325
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity counseling in medical school education: a systematic review

Abstract: BackgroundDespite a large evidence base to demonstrate the health benefits of regular physical activity (PA), few physicians incorporate PA counseling into office visits. Inadequate medical training has been cited as a cause for this. This review describes curricular components and assesses the effectiveness of programs that have reported outcomes of PA counseling education in medical schools.MethodsThe authors systematically searched MEDLINE, EMBASE, PsychINFO, and ERIC databases for articles published in Eng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
102
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(114 citation statements)
references
References 26 publications
7
102
0
5
Order By: Relevance
“…Green Prescription Initiative in New Zealand), understanding of specific benefits of exercise such as the safety of exercise in clinical populations and the awareness of the other health professionals who can assist in providing further PA advice. These findings are consistent with the results of recent studies and findings from a recent systematic review on PA counselling in medical school education (Dacey et al, 2014;Jones, Brooks & Wylie, 2013). The authors of the present study previously reported that New Zealand medical students had a good understanding of the links between exercise and health and positive attitudes towards PA advising in general practice (Mandic et al, 2017) and those outcomes were not changed considerably after the intervention in the present study.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Green Prescription Initiative in New Zealand), understanding of specific benefits of exercise such as the safety of exercise in clinical populations and the awareness of the other health professionals who can assist in providing further PA advice. These findings are consistent with the results of recent studies and findings from a recent systematic review on PA counselling in medical school education (Dacey et al, 2014;Jones, Brooks & Wylie, 2013). The authors of the present study previously reported that New Zealand medical students had a good understanding of the links between exercise and health and positive attitudes towards PA advising in general practice (Mandic et al, 2017) and those outcomes were not changed considerably after the intervention in the present study.…”
Section: Discussionsupporting
confidence: 82%
“…The effective medical education programmes incorporated experiential learning, theoretically based frameworks, and students' personal PA habits (Dacey et al, 2014). The heterogeneity of the PA-related curriculum and weak study design of previous studies (Dacey et al, 2014) warrant further examination of the effects of the inclusion of curricula on PA advising in medical education. The current study examined the effects of an introductory learning module on PA on knowledge, skills, and attitudes toward PA advising in third-year medical students in New Zealand.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Seventy one percent felt "physical activity" should be part of the regular curriculum. 9 Doctors are a respected source of health-related information and are well positioned to provide physical activity counselling to patients. Anand T et al, refers doctors as the potential agents to increase the levels of physical activity in large population and thus produce important health gains.…”
Section: Resultsmentioning
confidence: 99%